(untitled) (Journal of Information Technology and Digital World, 2022)
Humans are good at making millions of facial movements during conversation. In interpersonal relationships, the human emotion sensing system is vital. At an older age, automatic emotion recognition is a trendy research problem. Emotions are expressed through personas, hand and body gestures, and facial expressions. Emotion recognition via facial expressions is one of the most important fields in the human-machine interface. The strategy of recognizing emotions from facial expressions is known as facial expression analysis. Emotions are automatically perceived by the human brain, and software that can recognise emotions has recently been developed. This technology is constantly improving, and it will ultimately be able to sense emotions as accurately as human brains. The purpose of this work is to present a survey of emotion detection research using various machine learning techniques. It also summarises the benefits, drawbacks, and limitations of current approaches, as well as the concept’s evolution in research.